Data Assimilation of a Biological Model Using Genetic Algorithms - Thakur, Manoj; Deep, Kusum (Applications and Innovations in Intelligent Systems XIV, 2006)
In this paper the calibration of well known biological system namely Lotka-Volterra model is done using Genetic Algorithms. The problem of parameter estimation is formulated as an optimization problem, which is highly non linearand multimodal in nature. Binary Genetic Algorithms as well as Real Genetic Algorithms have been used to obtain the results.The comparative study showsthat the Real Genetic Algorithm is more promising.